Hybrid ionogels derived from polycationic polysilsesquioxanes for lithium ion batteries - Lee, Jin Hong; Lee, Albert S.; Hong, Soon Man; Hwang, Seung Sang; Koo, Chong Min (ELSEVIER SCI LTD, 2017)
A multifunctional crosslinkable and ionic-group functionalized ladder-like polysilsesquioxane was synthesized and utilized for the fabrication of hybrid ionogels for lithium ion batteries. The ionic-group functionalized ladder-like polysilsesquioxane combined the synergistic effects of hybrid materials in improving the thermal stability of conventional battery electrolytes, whilst maintain facile solution processability and chemically crosslinkable function in ionic conducting ionic liquid electrolyte media. Fabricated iongel electrolytes exhibiting exceptional thermal stability, mechanical properties, high ionic conductivity, and electrochemical stability. Lithium ion batteries fabricated with the hybrid ionic ladder like polysilsesquioxane ionogels exhibited initial discharge capacities on par with neat liquid electrolytes, good rate performance, as well as stable cyclability and excellent Coulombic efficiency. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: SOL-GEL REACTION; HEXAGONALLY STACKED STRUCTURE; ROD-LIKE POLYSILSESQUIOXANE; SOGGY-SAND ELECTROLYTES; POLYMER ELECTROLYTES; HIGH-PERFORMANCE; THERMOPLASTIC POLYSILSESQUIOXANES; COMPOSITE ELECTROLYTES; LIQUIDS; SILSESQUIOXANE